subtract 3 from 23 and u will get 20 then divide 2 by 2 and 2 by 20
x= 10
complette the square to get vertex form or y=a(x-h)^2+k
(h,k) is vertex
1. group x terms, so for y=ax^2+bx+c, do y=(ax^2+bx)+c
<span>
<span>
</span>
2, factor out the leading coefinet (constant in front of the x^2 term), basicallly factor out a
</span><span>
<span>
</span>
3. take 1/2 of the linear coefient (number in
front of the x), and square it ,then add negative and positive of it
inside parnthases
</span><span>
<span>
</span>
4. complete the squre and expand
</span>
so
y=-1/4x^2+4x-19
group
y=(-1/4x^2+4x)-19
undistribute -1/4
y=-1/4(x^2-16x)-19
take 1/2 of -16 and squer it to get 64 then add neg and pos inside
y=-1/4(x^2-16x+64-64)-19
factorperfect square
y=-1/4((x-8)^2-64)-19
expand
y=-1/4(x-8)^2+16-19
y=-1/4(x-8)^2-3
vertex is (8,-3)
Sqrt(8^2 + 3^2)
Y is 3,4
Z is -5,1
3-(-5) = 8 (difference between x coords)
4-1 = 3 (difference between y coords)
Equation is: sqrt( (xdiff)^2 + (ydiff)^2 )